2001
DOI: 10.1037/0278-7393.27.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Are emotionally charged lures immune to false memory?

Abstract: Using the Deese-Roediger-McDermott task and E. Tulving's (1985) remember-know judgments for recognition memory, the authors explored whether emotional words can show the false memory effect. Participants studied lists containing nonemotional, orthographic associates (e.g., cape, tape, ripe; part, perk, dark) of either emotional (e.g., rape) or nonemotional (e.g., park) critical lures. This setup produced significant false "remembering" of emotional lures, even though initially no emotional words appeared at st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
94
3
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 26 publications
(59 reference statements)
21
94
3
10
Order By: Relevance
“…More specifically, whilst our findings from typical participants replicated the observations of Pesta et al (2001), that the experience of illusory memories is attenuated for emotionally charged as compared to neutral words, we observed no such attenuation for participants with ASD 1 . In the context of our recent observation that individuals with ASD do not retain emotionally significant words in a qualitatively distinct fashion over time (Gaigg & Bowler, 2008), we interpret the current findings as follows.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…More specifically, whilst our findings from typical participants replicated the observations of Pesta et al (2001), that the experience of illusory memories is attenuated for emotionally charged as compared to neutral words, we observed no such attenuation for participants with ASD 1 . In the context of our recent observation that individuals with ASD do not retain emotionally significant words in a qualitatively distinct fashion over time (Gaigg & Bowler, 2008), we interpret the current findings as follows.…”
Section: Discussionsupporting
confidence: 75%
“…Half of these so-called Target Lures were neutral (e.g., Hook) and half of them were emotionally charged (e.g., 'Rape'). Pesta et al (2001) found that typical individuals were extremely unlikely to falsely identify the emotionally charged Target Lures as having been on the original study list whilst their false recognition rates of neutral Target Lures was far above chance. In other words, whilst the orthographic similarity between the studied words and the Target Lures gave rise to illusory memories of certain neutral words, the distinctive nature of the emotional words attenuated such illusory memories.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, although some studies have found that emotion enhances correct recognition accuracy (e.g., Ochsner, 2000), a number of others found no advantage for emotional material (Comblain, D'Argembeau, Van der Linden, & Aldenhoff, 2004;Pesta et al, 2001;Windmann & Kutas, 2001), and still others have found lower recognition accuracy for negative than neutral words (Maratos, Allen, & Rugg, 2000). Our findings add to the growing consensus that when pure-list designs are used, negative-emotional material does not enjoy an advantage in true recall or recognition relative to neutral words.…”
Section: Recognitionsupporting
confidence: 61%
“…In fact, false memory studies in which valence has been manipulated have revealed that participants are less likely to falsely recall and recognize negative-emotional critical lures as compared with neutral critical lures (e.g., Huang & Yeh, 2006;Kensinger & Corkin, 2004;Pesta, Murphy, & Sanders, 2001; but see Budson et al, 2006). Consistent with what we know about distinctiveness effects, the general explanation given for this finding concerns the distinctiveness of the emotional critical lures (e.g., Kensinger & Corkin, 2004).…”
supporting
confidence: 69%